Isolation and Identification of Endophytic Bacteria from Kumis Kucing Leaves (Orthosiphon aristatus Benth.) - Setiani, Nur Asni; Rafika Zahraeni; Siti Uswatun Hasanah (Biotropika: Journal of Tropical Biology, 2024)
Endophytic bacteria are in symbiosis with plants and have the potential to produce secondary metabolites similar to their host. Kumis kucing (Orthosiphon aristatus) is a traditional medicinal plant that has been proven to have many pharmacological activities, including antiviral and antibacterial. This study aims to isolate and characterize endophytic bacteria from kumis kucing leaves. Endophytic bacteria were isolated from kumis kucing leaf by spreading method on Trypticase Soy Agar (TSA) media and incubated for 24 hours at room temperature. Colonies that grew with bacterial morphology were inoculated on TSA media to obtain pure cultures. Pure cultures of isolates were identified through Gram staining, 16S rRNA gene sequencing, and bacterial growth curves. There were eight isolates with bacterial morphology, which were identified by Gram staining. The staining results showed that all were classified as Gram-negative with rod and coccus shapes. The 16S rRNA gene sequencing identified three bacterial isolates: Acinetobacter schindleri, Pantoea agglomerans, and Pseudomonas lurida. The three bacteria have different time to reach stationary phases in order to produce their secondary metabolites.